Effects of Chard (Beta Vulgaris L. Var. Cicla) on Cardiac Damage in Valproic Acid–Induced Toxicity. Issue 2 (7th October 2015) - Ustundag, Unsal Veli; Tunali, Sevim; Alev, Burcin; Ipekci, Hazal; Emekli‐Alturfan, Ebru; Akbay, Tugba Tunali; Yanardag, Refiye; Yarat, Aysen
Abstract: The aim of this study was to examine the effects of chard on valproic acid (VPA)‐induced cardiac damage. Female Sprague‐Dawley rats were grouped as control, chard given control (100 mg/kg/day, by gavage), VPA (500 mg/kg/day, intraperitoneally) and chard given VPA (100 mg/kg/day chard by gavage, 500 mg/kg/day VPA, intraperitoneally). The aqueous extracts of chard leaves were given 1 h prior to administration of VPA for 7 days. Malondialdehyde (MDA), total sialic acid (SA) levels and catalase (CAT) activity significantly increased in the VPA group compared with the control group ( P < 0.05). Chard administration significantly decreased MDA and SA levels in the control and in the VPA groups ( P < 0.05). Chard administration also significantly increased CAT activities and glutathione levels both in the control and in the VPA groups ( P < 0.05). As a conclusion, chard consumption may prevent cardiac tissue from oxidative stress and inflammation in VPA‐induced toxicity. Practical Applications: Valproic acid (VPA) is an antiepileptic drug and has severe toxic effects in experimental animals and humans. Chard ( B eta vulgaris L. var. cicla) has antioxidant, antidiabetic, antitumor and hepatoprotective effects. Its protective effects against VPA toxicity have not been fully investigated yet. According to the results of this study, chard ( B . vulgaris L. var. cicla) can be used as a dietary food supplement in the epilepsy treatment. The beneficial effect of chard consumption is an important finding in a nutritional point of view as chard contains many significant bioactive constituents for a healthy diet.